Service Learning Program : Culture Change at Balai Adat Indera Sakti in Penyengat Island - Satriadi Satriadi; Agung Nur Probohudono; Supriyono Supriyono; Rahmawati Rahmawati; Irmawati Irmawati; Siti Aisyah; Azra Ayue (Lembaga Pengembangan Kinerja Dosen, 2023)
Culture is one of the national identities that must be preserved and is a characteristic of a country that differentiates it from other countries. One of the cultures in Indonesia is Malay culture. Universiti Teknologi Malaysia (UTM) will visit Tanjungpinang, Indonesia with the agenda of carrying out Community Service on Penyengat Island which will be accompanied by lecturers and students from STIE Pembangunan Tanjungpinang. The aim of implementing Community Service is to introduce Malay culture to foreign students, especially Malay culture on Penyengat Island. This activity is carried out in the form of direct outreach. The results obtained from this Community Service activity were introducing Malay culture to overseas students with a series of activities involving lecturers, students and the residents of Penyengat Island.